Identificação de valores referência para métricas de softwares orientados por objetos - Tarcisio Guerra Savino Filó (2014)
Thresholds for the majority of software metrics are still not known. This might be the reason why a measurement method that should be part of a software quality assessment process is still not there in software industry. In this work, we applied a predefined empirical method to an 111 system dataset, identifying thresholds for 18 object-oriented software metrics. Furthermore, we proposed some improvements in that method. Differently from previous work, we have defined a catalogue of thresholds that gathers a greater amount of object-oriented software metrics, allowing the assessment of methods, classes and packages. Our approach suggests three ranges in the thresholds: Good/Common, Regular/Casual and Bad/Uncommon. The Good/Common range corresponds to values with high frequency. The Bad/Uncommon range corresponds to values with quite low frequency, and the Regular/Casual range is an intermediate one, which corresponds to values that are not too frequent neither have very low frequency. Although they do not necessarily express the best practices in Software Engineering, they reflect a quality standard followed by most of the evaluated software. To evaluate the effectiveness of the defined thresholds to indicate the real panorama of the software quality, we conducted three case studies and an experiment. The results suggest that the proposed thresholds can indicate the quality of the software, providing a benchmark for the quantitative assessment of the internal quality of object-oriented software, considering methods, classes and packages.